Assessment of degradation index in freeze-thaw damaged concrete using multi-channel contactless ultrasound. (26th September 2022) - Kim, Ryulri; Min, Jiyoung; Ahn, Eunjong; Choi, Hajin
Highlights: Efficient data acquisition framework for contactless ultrasonic testing utilizing multi-channel MEMS array. Introduction of Degradation Index based on leaky Rayleigh waves with increasing freeze-thaw damage in concrete. Numerical and experimental Validations with data obtained from freeze-thaw damaged concrete. Improvement of surface damage detection with ultrasound scanning compared to the point measurement-based methods. Abstract: Concrete is among the most widely used construction materials, especially in national infrastructure such as bridges, dams, and ports. This material fulfills an important role in ensuring the durability of structures that incorporate it. With recent climate change, issues related to degradation of concrete resulting from combined deterioration, e.g., freeze-thaw damage and chloride attack, have been increasingly reported, and, accordingly, there have been many studies focusing on the assessment of concrete durability using non-destructive testing. Non-contact ultrasonic testing measures leaky Rayleigh waves propagating through concrete, where the measurement procedure is a fully non-contact manner with the help of advanced sophisticated MEMS (Microelectromechanical systems) hardware technology. In the present study, a 64-channel non-contact ultrasonic system was developed to assess freeze-thaw damage of concrete elements, and an algorithm to assess concrete damage based on the velocities of leaky ultrasonic waves, the degradation index (DI), was proposed. The proposed system and algorithm were verified through a numerical analysis and experiments with varying degrees of freeze-thaw damage. The numerical analysis results showed that the velocity of ultrasonic waves, along with the degree of degradation, decreased with an increasing simulated damage ratio. The experimental freeze-thaw test results also confirmed that the DI was more sensitive to damage from the initial freeze-thaw cycles compared to the existing evaluation indexes, such as the relative dynamic elastic modulus.